THE TAX SYSTEM REFORMING FOR SMALL BUSINESSES - Snachov, M. P.; Verniuk, A. V. (Science and Transport Progress, 2008)
In the article some questions are considered concerning reformation of the taxation system of small businesses, the solution of them can improve the economy ofUkrainethrough the increase of quantity of small enterprises.